Trusted storytellers as freshwater restoration knowledge brokers: individual and collective voices can both be effective - Katharina Doehring; Cathy Cole; Paula Casanovas; Roger Young; Nancy Longnecker (Kōtuitui, 2024)
Aotearoa New Zealand's aquatic ecosystems are declining despite widespread awareness of mitigation needs. This study employs storytelling to address this issue, testing the role of the messenger in encouraging freshwater restoration in rural catchment communities. We quantified peer-to-peer knowledge exchange on three cognitive processes (retention and extraction of information, motivation to reproduce modelled restoration behaviour, and recall of acquired information), using ArcGIS® ‘StoryMaps’. We created two restoration stories; one told through the voice of a respected catchment group member known for leadership, and one through a collective catchment group voice. We surveyed freshwater community members (N = 82) before and after reading the stories, and one month later, and found that participants reading either catchment restoration story (1) accepted both the catchment collective and the respected individual member as a trusted source, and could therefore relate to either, and (2) thought the story was informative and contained new details, independent of the time span land holders have been actively restoring. While our study found no significant differences between individual or collective storytellers, it confirms the value of trusted messengers as restoration knowledge brokers in rural catchment communities, a critical step in value-led freshwater restoration at large scales.